(untitled) (Modern education and development, 2025)
In the 21st century, the English language has become more than just a subject taught in schools; it has evolved into a global tool of communication, especially among teenagers. Socialization — the process through which individuals interact, communicate, and build relationships — is deeply influenced by language. Among young people, English plays a vital role in shaping how they connect with peers locally and globally.